Menuju Swasembada Kedelai Melalui Penerapan Kebijakan yang Sinergis - I K. Tastra; Erliana Ginting; Gatot S.A. Fatah (Puslitbang Tanaman Pangan, 2012)
As a protein source and functional food, soybean has a strategic value in supporting sustainable national food security. Currently, domestic soybean production is only 32% of the national needs, while the balance is imported. Therefore, the improvement of soybean national production system as a sub-system of national food security is essential. The first step to improve the performance of soybean production system is to identify the main succeptible parameters that would dictate the sustainability of soybean production system leading to selfsufficiency. Strategic improvement of soybean production system should be performed through simultaneously empowering all parameters of component technologies so that the sinergic impacts can be gained by farmers as producers, processors/industries and users and consumers. However, this strategy needs support and appropriate policies from the government through reposition of BULOG (National Logistic Agency) function in soybean trade arrangement as well as providing price insentive to both farmers and soybean food processors in case of price fluctuation. This is similar to protection mechanism performed by some developed countries to their farmers. Using a simulation model, 15 scenarios are obtained to suit different agroecosystem of soybean producing areas leading to soybean self-sufficiency in 2015. Based on verification of this model using soybean production figures from 2009 to 2010, scenario 4 is selected which consists of a combination input of extended area program (15% per year), increase in productivity, population and soybean consumption ( 4%, 1.5% and 1.0% per year, respectively) and decrease of postharvest losses (2%).